Hubungan Status Gizi dan Asupan Mineral Kalsium terhadap Kejadian Dismenore pada Siswi MAN 3 Tulungagung - Kurniasari, Nadya Putri; Wirjatmadi, Bambang (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
Dysmenorrhea is a health disorder in the form of pain that often occurs in women. The prevalence of dysmenorrhea according to WHO is 90%. Based on previous research, there are several factors that cause dysmenorrhea such as nutritional status and calcium mineral intake level. MAN 3 Tulungagung is an educational institution in Tanen village, precisely on Supriyadi Street, Tanen village, Kec. Rejotangan, Kab. Tulungagung, East Java. Based on a survey that was conducted, 57 female students (67%) experienced dysmenorrhea. Through this study, researcher wanted to know the relationship between nutritional status and calcium mineral intake with the incidence of dysmenorrhea in female students of MAN 3 Tulungagung. This study uses a case control design. Subjects who participated in this study were 40 female students with 20 female students in each group. Data analysis used the chi square test. Result based on the analysis that has been done, there is a significant relationship with the incidence of primary dysmenorrhea in female students of MAN 3 Tulungagung with a p-value = 0.034 or <0.05, OR=7.364; CI:1.337-40.548. Then, there is a significant relationship between the level of calcium consumption and the incidence of primary dysmenorrhea in female students of MAN 3 Tulungagung with a p-value of 0.028* or <0.05, OR=6.000; CI:1.082-33.274. Adolescents should improve food intake and physical activity to improve nutritional status and calcium intake. This is important so that dysmenorrhea can be avoided and a better quality of life.